Consensus recommendations for the use of FEIBA® in haemophilia A patients with inhibitors undergoing elective orthopaedic and non‐orthopaedic surgery. (19th September 2012) - Rangarajan, S.; Austin, S.; Goddard, N. J.; Négrier, C.; Rodriguez‐Merchan, E. C.; Stephensen, D.; Yee, T. T.
Summary A growing number of publications have described the efficacy and safety of FEIBA as a first‐line haemostatic agent for surgical procedures in haemophilia A patients with high‐responding FVIII inhibitors. The aim of this study was to provide practical guidance on patient management and selection and also to communicate a standardized approach to the dosing and monitoring of FEIBA during and after surgery. A consensus group was convened with the aims of (i) providing an overview of the efficacy and safety of FEIBA in surgery; (ii) sharing best practice; (iii) developing recommendations based on the outcome of (i) and (ii). To date there have been 17 publications reporting on the use of FEIBA in over 210 major and minor orthopaedic and non‐orthopaedic surgical procedures. Haemostatic outcome was rated as 'excellent' or 'good' in 78–100% of major cases. The reporting of thromboembolic complications or anamnestic response to FEIBA was very rare. Key to the success of FEIBA as haemostatic cover in surgery is to utilize the preplanning phase to prepare the patient both for surgery and also for rehabilitation. Haemostatic control with FEIBA should be continued for an adequate period postoperatively to support wound healing and to cover what can in some patients be an extended period of physiotherapy. Published data have demonstrated that FEIBA can provide adequate, well tolerated, peri and postoperative haemostatic cover for a variety of major and minor surgical procedures in patients with haemophilia A. The consensus recommendations provide a standardized approach to the dosing and monitoring of FEIBA.